2007
DOI: 10.1159/000099068
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Homocysteine-Induced Oxidative Stress on Endothelial Function in Coronary Slow-Flow

Abstract: Background and Objective: Coronary slow-flow (CSF) phenomenon is characterized by delayed opacification of vessels in a normal coronary angiogram, but its etiopathogenesis remains unclear. Plasma homocysteine (Hcy) level can severely disturb vascular endothelial function and may play a role in the pathogenesis of CSF. In our study, endothelial function in patients with CSF and their relationship with Hcy and oxidative stress parameters are investigated. Method: Forty-four patients with angiographically proven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 53 publications
4
47
0
2
Order By: Relevance
“…Zeiher et al [14] claimed that in the early phases of atherosclerosis or in the patients with intensive coronary artery disease risk factors before the development of angiographically documented atherosclerotic disease, vasodilation capacity of coronary resistive arterioles by pharmacologic and physical stress was disturbed. Recently, we reported that homocysteine induced oxidative stress may impair endothelial function in patients with SCF [15]. In another study, we demonstrated that carotid intima-media thickness which is the early sign of atherosclerosis is increased in SCF [16].…”
Section: Discussionmentioning
confidence: 99%
“…Zeiher et al [14] claimed that in the early phases of atherosclerosis or in the patients with intensive coronary artery disease risk factors before the development of angiographically documented atherosclerotic disease, vasodilation capacity of coronary resistive arterioles by pharmacologic and physical stress was disturbed. Recently, we reported that homocysteine induced oxidative stress may impair endothelial function in patients with SCF [15]. In another study, we demonstrated that carotid intima-media thickness which is the early sign of atherosclerosis is increased in SCF [16].…”
Section: Discussionmentioning
confidence: 99%
“…These evaluations were made individually and in case of any discrepancy reassessment was done by a third cardiologist. The slow and normal coronary flow pattern limits accepted in literature were 36.2±2.6 frame for LAD, 36.2±2.6 frame for CX, and 20.4±3 frame for RCA (15,16). In this study the TFC exceeding these limits are accepted as SCF.…”
Section: Study Variablesmentioning
confidence: 90%
“…With respect to our results, during the evaluation of usage of basal enzyme levels (with the exception of CAT) it is argued that patient group with highest oxidative stress can be classified as coronary slow flow group. In all studies demonstrating the role of oxidative stress in these two patient groups, groups are assessed separately (15)(16)(17)(18). This is the first study to evaluate syndrome X and coronary slow flow comparing the results with normal controls.…”
Section: Discussionmentioning
confidence: 99%
“…Lp(a) is involved in the adhesion of inflammatory cells and migration and uptake of macrophage foam cells into the arterial wall 12) , and the Lp(a) level is positively associated with CAD events 13) . Homocysteine is an intermediate metabolite of methionine that contributes to cardiovascular disease via mechanisms such as endothelial dysfunction, increased lipid permeability and vascular inflammation 14,15) . Hyperhomocysteinemia is an independent risk factor for PAD and CAD 16,17) .…”
Section: Introductionmentioning
confidence: 99%